Biochemical and immunologic variables in patients with chronic or acute stress - Alina Banegas Cardero; Lillian Sierra Calzado (Centro Provincial de Información de Ciencias Médicas, 2017)
A descriptive and cross-sectional investigation of 64 patients older than 18 years, of which 31 presented neurosis (chronic stress) and 33 situational reaction (acute stress) who were diagnosed and assisted in the Psychiatry Department of "Dr. Juan Bruno Zayas Alfonso" Teaching General Hospital in Santiago de Cuba was carried out in the period of May to November, 2013, with the objective of determining the biochemical and immunologic variables of the blood tissue.  After obtaining blood tests in all the members of the series and of the statistical processing of the information by means of the percentage calculation, the mean and the standard deviation, it could be concluded that from the biochemical and immunologic points of view, immunoglobulinG increases in patients with situational reaction, while cortisol is increased in those that suffer from neurosis.